PENGARUH SPORT EDUCATION MODEL TERHADAP KEMAHIRAN BERMAIN SEPAK BOLA DAN KOMPETENSI INTERPERSONAL MAHASISWA - M. Said Zainuddin; Ahmad Zakaria; Andi Muhammad Fadlih (Journal of Physical Activity and Sports (JPAS), 2026)
Conventional collegiate soccer instruction often overemphasizes the mastery of isolated technical skills, thereby neglecting students' tactical understanding of gameplay and social domain development. This quasi-experimental study aims to examine the effect of the Sport Education Model (SEM) on students' soccer gameplay proficiency and interpersonal competence. The study employed a Pretest-Posttest Non-Equivalent Control Group Design involving college students divided into an experimental group (SEM-based instruction with a 16-session intervention phase) and a control group (conventional instruction). Soccer gameplay proficiency was measured using the Game Performance Assessment Instrument (GPAI) observation sheet, while interpersonal competence was evaluated through a validated questionnaire scale. Inferential analysis results indicate that students who participated in SEM-based instruction experienced a significant increase in gameplay proficiency particularly in decision-making and skill execution within authentic game situations while simultaneously demonstrating superior development in interpersonal competence regarding team communication, conflict resolution, and social responsibility compared to the control group. The implications of this study confirm that restructuring sports pedagogy through the authentic competitive climate and stable team affiliation inherent in SEM can effectively bridge the fulfillment of both motor and psychosocial learning outcomes in higher education.